Imaging strategies used in emergency departments for the diagnostic workup of COVID-19 patients during the first wave of the pandemic: a cost-effectiveness analysis. (December 2022) - Kepka, Sabrina; Zarca, Kevin; Viglino, Damien; Marjanovic, Nicolas; Taheri, Omide; Peyrony, Olivier; Desmettre, Thibaut; Wilme, Valérie; Marx, Tania; Muller, Joris; Harscoat, Sebastien; Le Borgne, Pierrick; et al.
Abstract: Objectives: Emergency departments (EDs) were on the front line for the diagnostic workup of patients with COVID-19–like symptoms during the first wave. Chest imaging was the key to rapidly identifying COVID-19 before administering RT-PCR, which was time-consuming. The objective of our study was to compare the costs and organizational benefits of triage strategies in ED during the first wave of the COVID-19 pandemic. Methods: We conducted a retrospective study in five EDs in France, involving 3712 consecutive patients consulting with COVID-like symptoms between 9 March 2020 and 8 April 2020, to assess the cost effectiveness of imaging strategies (chest radiography, chest computed tomography (CT) scan in the presence of respiratory symptoms, systematic ultra–low-dose (ULD) chest CT, and no systematic imaging) on ED length of stay (LOS) in the ED and on hospital costs. The incremental cost-effectiveness ratio was calculated as the difference in costs divided by the difference in LOS. Results: Compared with chest radiography, workup with systematic ULD chest CT was the more cost-effective strategy (average LOS of 6.89 hours; average cost of €3646), allowing for an almost 4-hour decrease in LOS in the ED at a cost increase of €98 per patient. Chest radiography (extendedly dominated) and RT-PCR with no systematic imaging were the least effective strategies, with an average LOS of 10.8 hours. The strategy of chest CT in the presence of respiratory symptoms was more effective than the systematic ULD chest CT strategy, with the former providing a gain of 37 minutes at an extra cost of €718. Discussion: Systematic ULD chest CT for patients with COVID-like symptoms in the ED is a cost-effective strategy and should be considered to improve the management of patients in the ED during the pandemic, given the need to triage patients.